Study of mental health outcomes associated with different brands of venlafaxine at the Kumeu medical centre from January 2017 to October 2018. (May 2020) - Ferguson, William; Clapshaw, Lesley
Background: The antidepressant venlafaxine has been available in New Zealand for two decades and is funded by the New Zealand Drug Purchasing Agency PHARMAC. This audit aimed to determine whether change to a different funded generic formulation of venlafaxine affected patient responses to venlafaxine. Methods: A retrospective review of patient records for all patients at Kumeu Medical Centre, Auckland, New Zealand who received a prescription for venlafaxine since January 2017 was performed. Outcomes for patients who had experienced a stable positive clinical response to either of the two previously funded venlafaxine formulations and who were switched to the newly funded formulation were summarised. Results: Of 49 patients who had been prescribed venlafaxine, 34 patients were excluded; 15 patients had experienced a stable positive clinical response to either of the two previously funded venlafaxine formulations and switched to the newly funded formulation. Of these, 12 (80%) had poor outcomes following the change in venlafaxine formulation. Nine patients switched back to the original brand venlafaxine and showed improvement in clinical symptoms. Conclusion: These cases, reported from a single general practice, should be sufficient to call attention to the possibility of loss of effectiveness for patients treated with a funded generic brand of venlafaxine, and the need for further research.